Vida y subjetividad: Los Descartes de Michel Henry - Lipsitz, Mario (ARFIL y UNL, 2018)
With the cogito ergo sum, Descartes has intended to offer a safe ground for the construction of scientific knowledge. Nevertheless, the problematic thus posed has totally forgotten, as Heidegger points out, to elucidate the sense of the being of this sum. It can be said that the whole work of Michel Henry constitutes a deeply original attempt to raise the question of the ego sum on a truthfully ontological context. Hence, his meditation on Descartes work and project takes up a central and permanent place in his work. Henry discovers to us in L’essence de la Manifestation (1964) and in Phénoménologie du Corps (1965) a Descartes whose project, based unreflectively on an intuitionist procedure, identifies truth with evidence and thus predetermines his investigation as an impossible attempt to exhibit the grounding under light, which is impossible, given that the grounding, the being of the ego — Henry states-, is invisible. This is what Descartes has understood, according to Henry’s  “Généalogie de la Psychanalysé9” (1985): the being of the sum is not a  “that” which may be given by a vision but a  “how” that reveals itself without any mediation as pathos-, the appearing of life to itself in the immanence of its affectivity.